A crack-free and super-hydrophobic cathode micro-porous layer for direct methanol fuel cells. (15th January 2015) - Yan, X.H.; Zhao, T.S.; An, L.; Zhao, G.; Zeng, L.
Highlights: A crack-free and super-hydrophobic cathode MPL is proposed. The new MPL enables a significant increase in the water recovery flux. The use of the new MPL improves the power density by more than 30%. Abstract: A critical issue in operating passive direct methanol fuel cells (DMFCs) with neat methanol is finding a way to passively transport water generated at the cathode to the anode through membranes. This is so that the water required for anodic methanol oxidation can be compensated. The corresponding water flux depends on the capillary pressure created by the cathode micro-porous layer (MPL). Conventional MPLs made of carbon powder suffer from the problem of mud-cracks, significantly reducing the capillary pressure. In this work, we propose a cathode MPL prepared with fluorinated carbon nanotubes. It is demonstrated that the fluorinated nanotube MPL has no mud-cracks and its contact angle is as high as 153°. The application of the crack-free and super-hydrophobic MPL to a passive DMFC operating with neat methanol enables a significant increase in the water recovery flux, improving the anodic methanol oxidation reaction and thereby boosting the cell performance.